Diversity of Coral-Associated Fauna II - Montano, Simone (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Coral reefs are one of the most diverse types of ecosystems on Earth and one of the richest in terms of species interactions. This Special Issue aims to elucidate the hidden diversity of coral reefs through the description of new associations involving coral reef framework taxa.